Toll-like receptor–4 gene polymorphisms in Javanese aggressive and chronic periodontitis patients - Chiquita Prahasanti (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Tool-like receptor-4 (TLR4) gene polymorphisms affect the ability of the host in response to pathogenic bacteria, and can also be associated with the severity of periodontitis. TLR4 gene polymorphisms (Asp299Gly and Thr399Ile) are ones of gene mutations that occur in patients with aggressive periodontitis. Purpose: To investigate the involvement of TLR4 gene polymorphism as a risk factor of aggressive and chronic periodontitis of Javanese population in Surabaya. Method: This research can be considered as an analytic observational study, with a case-control study design in patients with aggressive periodontitis and chronic periodontitis. DNA samples were derived from peripheral blood. TLR4 gene polymorphisms (Asp299Gly and Thr399Ile) were then observed by PCR-RFLP. Result: There was no TLR4 gene polymorphism (Asp299Gly) in the whole samples. And, based on the results of simple logistic regression analysis on TLR4 gene polymorphisms (Thr399Ile), mutants heterozygote and homozygote obtained had OR value about 0.25. Conclusion: In Surabaya, there was no heterozygote and homozygote mutant in TLR4 gene polymorphisms, (Asp299Gly) and (Thr399Ile), that can be considered as risk factors of chronic periodontitis.